Intellectualisation of indigenous language Sesotho at a South African university and implications for the speakers - Ngubane, Nomalungelo (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2024)
The persistent underdevelopment of African indigenous languages in South Africa denies students who are the speakers of these languages access to education in their mother tongues. Denying students access to education in their preferred languages is an infringement of their birth right enshrined in the Constitution. The circumstances are even worse when a foreign language English is the only language recognised for teaching and learning in South African higher education. Learning in a foreign language has been identified as a major barrier to effective learning, a cause for academic under-achievement and high attrition rates in higher education. Underpinned by the Language Management Theory, this conceptual paper discusses an institutional language policy plan of a university in South Africa, whose intention is to develop and intellectualise an African indigenous language Sesotho as an academic language so that it can be used by the speakers for epistemological access and success. There is limited literature on the intellectualisation of Sesotho. The paper draws from the work of other scholars who have written on the intellectualisation of African indigenous languages to strengthen the arguments on the importance of the intellectualisation of Sesotho in one university in South Africa, the processes followed, and the implications for the speakers. The paper hopes to make contributions to the ongoing debates on the intellectualization of African indigenous languages, especially in South Africa.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 3, Volume 8, 2024 Special Issue
Keywords: Language intellectualisation; African languages; Sesotho; Language Management Theory; Terminology development; Higher education; African languages; Education, Higher -- South Africa; Indigenous peoples -- Languages; Sotho language